Transnasal endoscopy for direct visual control of esophageal stent placement without fluoroscopy - Borgulya, M.; Ell, C.; Pohl, J. (Endoscopy, 2012)
Placement of self-expanding metal stents (SEMSs) is a well-established treatment for esophageal stenosis and postoperative anastomotic leaks. Conventional endoscopic procedures for SEMS placement require fluoroscopic guidance, but transnasal endoscopy (TNE) with ultraslim endoscopes may allow precise stent release under direct visual control without the need for fluoroscopy. This prospectively collected data investigated the feasibility and safety of TNE-guided SEMS placement without fluoroscopy. Between March 2009 and February 2011, 20 consecutive patients underwent TNE-guided SEMS placement without fluoroscopy. The technical success rate was 100 % and no fluoroscopy was required during the procedures. Five patients underwent SEMS placement as a bedside procedure in the intensive care unit. The mean intervention time was 13.4 minutes (range 6 – 26) and there were no early complications. In summary, TNE-guided SEMS placement allows precise stent placement without fluoroscopic control and can therefore be performed as a simple bedside procedure.